Gene and Chromosomal Copy Number Variations as an Adaptive Mechanism Towards a Parasitic Lifestyle in Trypanosomatids - Reis-Cunha, Joao L.; Valdivia, Hugo O.; Bartholomeu, Daniella Castanheira (Current Genomics, 2018)
Trypanosomatids are a group of kinetoplastid parasites including some of great public health importance, causing debilitating and life-long lasting diseases that affect more than 24 million people worldwide. Among the trypanosomatids, Trypanosoma cruzi, Trypanosoma brucei and species from the Leishmania genus are the most well studied parasites, due to their high prevalence in human infections. These parasites have an extreme genomic and phenotypic variability, with a massive expansion in the copy number of species-specific multigene families enrolled in host-parasite interactions that mediate cellular invasion and immune evasion processes. As most trypanosomatids are heteroxenous, and therefore their lifecycles involve the transition between different hosts, these parasites have developed several strategies to ensure a rapid adaptation to changing environments. Among these strategies, a rapid shift in the repertoire of expressed genes, genetic variability and genome plasticity are key mechanisms. Trypanosomatid genomes are organized into large directional gene clusters that are transcribed polycistronically, where genes derived from the same polycistron may have very distinct mRNA levels. This particular mode of transcription implies that the control of gene expression operates mainly at post-transcriptional level. In this sense, gene duplications/losses were already associated with changes in mRNA levels in these parasites. Gene duplications also allow the generation of sequence variability, as the newly formed copy can diverge without loss of function of the original copy. Recently, aneuploidies have been shown to occur in several Leishmania species and T. cruzi strains. Although aneuploidies are usually associated with debilitating phenotypes in superior eukaryotes, recent data shows that it could also provide increased fitness in stress conditions and generate drug resistance in unicellular eukaryotes. In this review, we will focus on gene and chromosomal copy number variations and their relevance to the evolution of trypanosomatid parasites.
Keywords: Kinetoplastid parasites